2019
DOI: 10.1002/jcb.28161
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐29b regulates hypertrophy of murine mesenchymal stem cells induced toward chondrogenesis

Abstract: Objective Chondrocyte hypertrophy, a terminal stage of chondrocyte differentiation, is essential to the endochondral bone formation and is one of the major pathological factors in osteoarthritis. This study investigated the role of microRNA‐29b (miR‐29b), which is involved in chondrogenesis, in the regulation of hypertrophy in chondrocytes. Methods miR‐29b expression was assessed during murine mesenchymal stem cells (mMSCs) chondrogenesis. To detect whether miR‐29b affects chondrocyte hypertrophy, the mMSCs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…They are also involved in chondrogenic differentiation of hBMSCs. For example, miR-29b, possibly via its target gene histone deacetylase 4 (HDAC4), promotes the hypertrophic phenotype [19]. Overexpression of miR-145 in C3H10T1/2 cells reduced SOX9 expression, thus significantly suppressing cartilage matrix synthesis in vitro [20].…”
Section: Introductionmentioning
confidence: 99%
“…They are also involved in chondrogenic differentiation of hBMSCs. For example, miR-29b, possibly via its target gene histone deacetylase 4 (HDAC4), promotes the hypertrophic phenotype [19]. Overexpression of miR-145 in C3H10T1/2 cells reduced SOX9 expression, thus significantly suppressing cartilage matrix synthesis in vitro [20].…”
Section: Introductionmentioning
confidence: 99%
“…as Col10a1 [44][45][46]. These researches implicated that AA might also alleviate hypertrophic differentiation via keeping the expression of SOX9 in balance.…”
Section: Discussionmentioning
confidence: 97%
“…Future work is expected to explore the exact mechanism of AA on regulating chondrocyte differentiation. Beyond that, the study has shown that SOX9 can both interact directly with and suppress Runx2 activity and other genes related to hypertrophic chondrocytes, such as Col10a1 [47][48][49]. These researches implicated that AA might also alleviate hypertrophic differentiation via keeping the expression of SOX9 in balance.…”
Section: Discussionmentioning
confidence: 98%